A Parallel of Patient Proactivity Behaviours and Attitudes between the Republic of South Africa and the United States of America - Bisschoff, Christo; Fullerton, Sam (International Review of Management and Marketing, 2017)
This study compares patient propensity towards proactive health behaviour of South Africans and Americans. While the health care system of South Africa is severely stretched to deliver medical services, the United States maintains high levels of medical services for their countrymen, hence enjoying a much higher life expectancy. The South Africa data consisted of a snowball social media campaign resulting in 180 responses while the United States data consists of 1,031 responses from the general adult population of the country. Some were analysed from the United States. Both groups display a propensity towards proactive health behaviour while differing only on how ill they really are before deciding to see a doctor. The more important factors in South Africa were: Health is my own responsibility, Preventative health, and Information on illnesses, while the Americans identified: Early diagnosis, Preventive treatment and Consulting electronic information. Although both groups are sensitive to proactive attitudes and behaviours, there are differences between the latent variables the importance of the variables. The Americans seem to be much more inquisitive, and they seem to gather more information on health issues than the South Africans. The Americans also tend to react faster to arising health issues. Keywords: proactivity; health; healthcare JEL Classifications: I12, I14